STAT3 antisense oligonucleotide AZD9150 in a subset of patients with heavily pretreated lymphoma: results of a phase 1b trial. Issue 1 (16th November 2018) - Reilley, Matthew J.; McCoon, Patricia; Cook, Carl; Lyne, Paul; Kurzrock, Razelle; Kim, Youngsoo; Woessner, Richard; Younes, Anas; Nemunaitis, John; Fowler, Nathan; Curran, Michael; Liu, Qinying; et al.
Abstract : Background: The Janus kinase (JAK) and signal transduction and activation of transcription (STAT) signaling pathway is an attractive target in multiple cancers. Activation of the JAK-STAT pathway is important in both tumorigenesis and activation of immune responses. In diffuse large B-cell lymphoma (DLBCL), the transcription factor STAT3 has been associated with aggressive disease phenotype and worse overall survival. While multiple therapies inhibit upstream signaling, there has been limited success in selectively targeting STAT3 in patients. Antisense oligonucleotides (ASOs) represent a compelling therapeutic approach to target difficult to drug proteins such as STAT3 through of mRNA targeting. We report the evaluation of a next generation STAT3 ASO (AZD9150) in a non-Hodgkin's lymphoma population, primarily consisting of patients with DLBCL. Methods: Patients with relapsed or treatment refractory lymphoma were enrolled in this expansion cohort. AZD9150 was administered at 2 mg/kg and the 3 mg/kg (MTD determined by escalation cohort) dose levels with initial loading doses in the first week on days 1, 3, and 5 followed by weekly dosing. Patients were eligible to remain on therapy until unacceptable toxicity or progression. Blood was collected pre- and post-treatment for analysis of peripheral immune cells. Results: Thirty patients were enrolled, 10 at 2 mg/kg and 20 at 3 mg/kg dose levels. Twenty-seven patients had DLBCL. AZD9150 was safe and well tolerated at both doses. Common drug-related adverse events included transaminitis, fatigue, and thrombocytopenia. The 3 mg/kg dose level is the recommended phase 2 dose. All responses were seen among DLBCL patients, including 2 complete responses with median duration of response 10.7 months and 2 partial responses. Peripheral blood cell analysis of three patients without a clinical response to therapy revealed a relative increase in proportion of macrophages, CD4+, and CD8+ T cells; this trend did not reach statistical significance. Conclusions: AZD9150 was well tolerated and demonstrated efficacy in a subset of heavily pretreated patients with DLBCL. Studies in combination with checkpoint immunotherapies are ongoing. Trial registration: Registered at ClinicalTrials.gov: NCT01563302 . First submitted 2/13/2012.